Implementation of Augmented Reality Technology on Business Cards Using Blender and OpenSpace 3D - Rosemalatriasari, Ari (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
Business cards are the identity of a business person and also a link between clients and your business. Currently Augmented Reality (AR) is developing rapidly in various fields. One application of AR is in the field of creative industry. This Augmented Reality application for business cards is one of the innovations that can make conventional business cards into a more interactive business card. This business card is made using Blender and OpenSpace 3D. Based on the test results, this AR application is successfully run and can display several features, such as location links, blog addresses, and company websites. Based on the questionnaire testing, 85% stated that business people strongly support and agree that this application is appropriate to be implemented as an interactive business card.